Effect of heavy metal model mixture on haematological parameters of Labeo rohita from Gharni Dam Nalegaon, Latur - Chandanshive, S S; Sarwade, P P; Humbe, Atul; Mohekar, A D (International Multidisciplinary Research Journal, 2012)
The present study of heavy metal model mixture on fish experimental changes in blood haematological parameters (Viz. WBC, RBC and Haematocript) of the laboratory acclimatized fish Labeo rohita, exposed to different heavy metals mixture model were studied. Erythrocyte count decreased significantly (p < 0.005) in the blood of fish exposed to almost all Heavy metal model mixture concentrations studied while alterations of haematocrit level depended on Heavy metal model mixture concentration. The highest concentration of Heavy metal model mixture (21.79%) induced a drop in haematocrit level meanwhile the level of haematocrit in blood of fish exposed to all lower Heavy metal model mixture concentrations was higher as compared to control. Erythrocyte count in the blood of Heavy metal model mixture-exposed fish was significantly lower as compared to control, even in fish exposed to the lowest concentration of Heavy metal model mixture (1.1%).